2022
DOI: 10.2903/j.efsa.2022.7244
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a feed additive consisting of Bacillus velezensis ATCC PTA‐6737 (Bacillus velezensis PB6) for turkeys for fattening, turkeys reared for breeding, laying hens, minor poultry species for laying, piglets (weaned), weaned minor porcine species and sows (Kemin Europe N.V.)

Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of Bacillus subtilis ATCC PTA‐6737 (Bacillus subtilis PB6) when used as a feed additive for turkeys for fattening, turkeys reared for breeding, laying hens, minor poultry species for laying, piglets (weaned), weaned minor porcine species and sows. With this application, the company requested the modification of the current authorisations as regards the strain taxonomy from B. subtilis ATC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In the previous assessments (EFSA FEEDAP Panel, 2012a , 2013 , 2017a , 2020 , 2022 ), the active agent B. velezensis ATCC PTA‐6737 was presumed safe for the target species, consumers and the environment based on the qualified presumption of safety (QPS) approach (EFSA, 2007 ; EFSA BIOHAZ Panel, 2023 ).…”
Section: Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous assessments (EFSA FEEDAP Panel, 2012a , 2013 , 2017a , 2020 , 2022 ), the active agent B. velezensis ATCC PTA‐6737 was presumed safe for the target species, consumers and the environment based on the qualified presumption of safety (QPS) approach (EFSA, 2007 ; EFSA BIOHAZ Panel, 2023 ).…”
Section: Assessmentmentioning
confidence: 99%
“…In 2022, the FEEDAP Panel concluded that the additive is non‐irritant to skin and eyes or a dermal sensitiser, but it should be considered a respiratory sensitiser (EFSA FEEDAP Panel, 2022 ). The Panel notes that the OECD test guidelines available at present are designed to assess the skin sensitisation potential of chemical substances only and that, currently, no validated assays for assessing the sensitisation potential of microorganisms are available.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, the FEEDAP Panel concluded that the additive was non‐irritant to skin and eyes or a dermal sensitiser, but it should be considered a respiratory sensitiser (EFSA FEEDAP Panel, 2022 ). The Panel notes that the OECD test guidelines available at present are designed to assess the skin sensitisation potential of chemical substances only and that currently no validated assays for assessing the sensitisation potential of microorganisms are available.…”
Section: Assessmentmentioning
confidence: 99%
“…An opinion on the compatibility of Bacillus subtilis PB6 ( Bacillus subtilis ATCC PTA‐6737) with coccidiostats was also published in 2010 (EFSA FEEDAP Panel, 2010 ) and recently, an opinion with the modification of the strain designation from Bacillus subtilis ATCC PTA‐6737 to Bacillus velezensis ATCC PTA‐6737 (EFSA FEEDAP Panel, 2022 ).…”
Section: Introductionmentioning
confidence: 99%